Challenges to Peacebuilding - United Nations University (United Nations, 2006)
Many ceasefires and peace agreements in civil conflict are initially unsuccessful. Some give way to renewed, and often escalating, violence. In other cases, peace processes have become interminably protracted. This study approaches the problem by focusing on 'spoilers': groups and tactics that actively seek to obstruct or undermine conflict settlement through a variety of means, including terrorism and violence. It considers why spoilers and spoiling behaviour emerge and how they can be addressed, drawing upon experience from Northern Ireland, the Basque region, Bosnia, Colombia, Israel-Palestine, Cyprus, the Caucasus and Kashmir.